A Phylogenetic and Phenotypic Analysis of Salmonella enterica Serovar Weltevreden, an Emerging Agent of Diarrheal Disease in Tropical Regions. - Carine Makendi; Andrew J Page; Brendan W Wren; Tu Le Thi Phuong; Simon Clare; Christine Hale; David Goulding; Elizabeth J Klemm; Derek Pickard; Chinyere Okoro; Martin Hunt; Corinne N Thompson; et al. (Public Library of Science (PLoS), 2016)
Salmonella enterica serovar Weltevreden (S. Weltevreden) is an emerging cause of diarrheal and invasive disease in humans residing in tropical regions. Despite the regional and international emergence of this Salmonella serovar, relatively little is known about its genetic diversity, genomics or virulence potential in model systems. Here we used whole genome sequencing and bioinformatics analyses to define the phylogenetic structure of a diverse global selection of S. Weltevreden. Phylogenetic analysis of more than 100 isolates demonstrated that the population of S. Weltevreden can be segregated into two main phylogenetic clusters, one associated predominantly with continental Southeast Asia and the other more internationally dispersed. Subcluster analysis suggested the local evolution of S. Weltevreden within specific geographical regions. Four of the isolates were sequenced using long read sequencing to produce high quality reference genomes. Phenotypic analysis in Hep-2 cells and in a murine infection model indicated that S. Weltevreden were significantly attenuated in these models compared to the classical S. Typhimurium reference strain SL1344. Our work outlines novel insights into this important emerging pathogen and provides a baseline understanding for future research studies.